Rethinking Online Radicalization - Whittaker, Joe (Perspectives on terrorism, 2022)
This article seeks to re-ontologize online radicalization. Individuals becoming terrorists after being exposed to online content have become a prescient concern for academics, policy makers, and journalists. Existing theoretical contributions to the concept have assumed that there are two ontological domains—online and offline—that can be meaningfully separated. This article will draw from several arguments from other fields which critique this position; the contemporary information environment enmeshes the two inseparably. This argument is then advanced to demonstrate that online radicalization is a redundant concept by drawing on empirical research as well as recent case studies of terrorism. Instead, scholars should consider holistic theories which account for a range of other factors beyond online communication technologies.